2015
DOI: 10.1515/ncrs-2014-9042
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of dichloro-N,N-bis(pyridine-2-ylmethyl)cyclohexamino copper(II), C18H23Cl2CuN3

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…On the one hand, a survey of the CSD revealed that, in the few known penta-coordinated [Zn­(R-bpa)­Br 2 ] complexes, the bpa ligand is bound to the central metal as mer -isomer. ,,,, On the other hand, even for a significantly broader class of compounds, namely, [M­(R-bpa)­X 2 ] complexes containing any transition metal M or any halogen ions X, the bpa fac -isomer was found relatively rarely in the solid state, with only a handful of structures in the literature. , …”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, a survey of the CSD revealed that, in the few known penta-coordinated [Zn­(R-bpa)­Br 2 ] complexes, the bpa ligand is bound to the central metal as mer -isomer. ,,,, On the other hand, even for a significantly broader class of compounds, namely, [M­(R-bpa)­X 2 ] complexes containing any transition metal M or any halogen ions X, the bpa fac -isomer was found relatively rarely in the solid state, with only a handful of structures in the literature. , …”
Section: Resultsmentioning
confidence: 99%